The dynamics of international capital flows: Results from a dynamic hierarchical factor model - Marcel Förster; Markus Jorra; Peter Tillmann (Philipps-University Marburg, Faculty of Business Administration and Economics, 2012)
The present paper examines the degree of comovement of gross capital inflows, which is a highly sensitive issue for policy makers. We estimate a dynamic hierarchical factor model that is able to decompose inflows in a sample of 47 economies into (i) a global factor common to all types of flows and all recipient countries, (ii) a factor specific to a given type of capital inflows, (iii) a regional factor and (iv) a country-specific component. We find that the latter explains by far the largest fraction of fluctuations in capital inflows followed by regional factors, which are particularly important for emerging markets' FDI and portfolio inflows as well as bank lending to emerging Europe. The global factor, however, explains only a small share of overall variation. The exposure to global drivers of capital flows, i.e. the global factor and the factor specific to each type of capital inflows, is particularly pronounced for countries with a more developed financial system. A fixed exchange rate regime does not shield countries from the ebb and flow of global capital flow cycles.
Keywords: F21; F32; C30; 330; Capital flows; dynamic hierarchical factor model; emerging economies; financial crises; Kapitalmobilität; Kapitalimport; Standortfaktor; Aufstrebende Märkte; Finanzmarktkrise; Schätzung; Welt